Factors Associated With Academic Achievement In Urban Primary School Children With Special Reference To Iron Status And Blood Lead Concentrations - M. S. Flailih, Abdelhamid (2001)
The overall aim of the study was to examine the relationship between iron status, blood lead concentration and academic achievement of selected urban primary school children. The specific objectives were to assess the iron status and blood lead concentration of subjects and to determine the relationship between these parameters and their academic achievement. In addition, other factors such as socioeconomic status were examined. Study subjects were 108 (47 male and 61 female) aged 132 ± 9 months with good health and nutritional status. Study subjects were urban Malay primary school children attending two schools (Sekolah Kebangsaan lalan Pasar 1 and Sekolah Kebangsaan lalan Pasar 2) in Kuala Lumpur. Five-ml venous blood sample was collected from each subject. The hematological parameters (hemoglobin and hematocrit) were measured by using the Cyanmethemoglobin and M icrohematocrit methods respectively. The biochemical indices of iron status (serum iron, serum ferritin and total iron-binding capacity) were measured by using the methods of colorimetric test with Ferrozin®/ascorbic acid, IMX® Ferritin assay-Micropartical Enzyme Immunoassay (MEIA), and